The tissue structure of the vegetative organs of strawberry (Fragaria moschata Duch®) - J. Papp; I. Lenkefi; M. Gara; P. Gracza (International Journal of Horticultural Science, 2000)
The tissue structure of the vegetative organs of strawberry (root, rhizome, stolon, leaf) is discussed in this paper. The authors stated that the root structure described by Muromcev (1969) and Naumann-Seip (1989) develops further from the primary structure. It grows secondarily and the transport tissue becomes continuous having ring shape. In the primary cortex of the rhizome periderm like tissue differentiates, but according to the examinations up to now, it does not take over the role of the exodermis. The exodermis is phloboran filled primary cortex tissue with 3-4 cell rows under the rhizodermis. The development of the transport tissue of the petiole is also a new recognition. In the lower third of the petiole the transport tissue consists of 3 collaterally compound vascular bundles. In the middle third there are 5 bundles because of the separation of the central bundle and in the upper third of the petiole 7 bundles can be observed because of the ramification of the outside bundles. Therefore attention must be taken also in the case of other plants at making sections. There might be confusions in the results of the examinations if the number of bundles increases in the petiole. The tissue structure might vary depending on the origin of the tissue segment.